Batee Jirat-Batu Aceh Islamic Gravestones in Sultanate Banten Building New Historiography Aceh and Banten Relationship - Arifia, Sariat; Mizuar, Mizuar; Munawir, Munawir; Ahyadi, Yadi; Akmal, Aslim (Ridwan Institute, 2024)
Othman Yatim's research has provided a clear picture of the influence of Acehnese stones, which are so abundant in the Malaysian peninsula, but on the other hand, there is still a need to carry out a more in-depth comparative study regarding the existence of similar tombstones in Indonesia, especially on the island of Java. On the island of Java itself, the Sultanate of Banten is the only kingdom whose sultans or kings have used Batee Jirat Batu Aceh typology tombstones for generations, from the beginning to the end of the Sultanate. Therefore, comparative research was carried out on similar tombstones in Aceh, and then an analysis of the reconstruction of past relations between Aceh and Banten, as the Big Spice City, which also played a major role in the spread of Islam in Indonesia, was carried out.